New-onset cutaneous lichen planus following Vaxzevria (Oxford-AstraZeneca) COVID-19 vaccination - Amira Muftah; Stephen Lee; Mariam Abbas (SAGE Open Medical Case Reports, 2024)
We report a 56-year-old male who developed cutaneous lichen planus (LP) following Vaxzevria (Oxford-AstraZeneca) COVID-19 vaccination. Multiple topical and systemic therapies were tried with limited success; however, partial improvement was observed with narrow-band UVB (NB-UVB) phototherapy. This report adds to the growing evidence of new-onset LP following COVID-19 vaccination and underscores the need for careful reporting, monitoring, and management of vaccine-related adverse effects.